PERPAJAKAN SEDERHANA BAGI GURU DI KAWASAN WISATA BANTAR AGUNG - Mohammad Sigit Adi Nugraha; Wardhani Indah Sari; Dedy Suryadi; Moh. Abdurrosyid; Efrinal Efrinal (JURNAL ABDIMAS PLJ, 2026)
Bantaragung Village is a rapidly growing tourist village area in Majalengka Regency. Along with the increase in economic and tourism activities, the demand for legal awareness and fulfillment of administrative obligations, including taxation, is becoming increasingly crucial. Teachers, as the main pillar of education, hold a strategic role as agents of change, yet they often face obstacles in understanding dynamic tax regulations and reporting procedures that are perceived as complex. Objective: This study aims to analyze the application, understanding, and urgency of simple tax education for teachers in the Bantaragung tourist area to increase voluntary tax compliance. Method: The method used in this activity is a descriptive qualitative approach combined with socialization and assistance implementation methods (action research). The research subjects consisted of teachers across education levels in Bantaragung Village. Data were collected through pre-test and post-test questionnaires, in-depth interviews, and direct observation during the simulation of filling out e-Filing for Income Tax (PPh) Article 21. Results: The results showed that prior to the simple tax education program, the majority of teachers experienced administrative anxiety and confusion regarding the calculation of PTKP (Non-Taxable Income) and digital-based reporting mechanisms. After being provided with assistance using simplified practical tax modules, there was increase in regulatory understanding, and the success rate of independent Annual Tax Return (SPT). Tax education targeting educators in this tourist area has proven effective in creating new tax literacy agents who have the potential to spread tax awareness to the tourism-aware community (Pokdarwis) and local MSME actors around Bantaragung.